Proceedings of the 2nd International Scientific Conference on New Industrialization: Global, National, Regional Dimension (SICN 2019
DOI: 10.2991/sicni-18.2019.131
|View full text |Cite
|
Sign up to set email alerts
|

Employment of persons with disabilities in the new industrialization (by the example Omsk region

Abstract: The employment conditions of persons with disabilities are influenced by modern trends in the transformation of social and labor relations associated with the new industrialization and digitalization, social policy aimed at improving the quality of life of this category of persons and legislative changes. So, in the Omsk region it is planned to change the quota of jobs for people with disabilities. The purpose of the study, thus, was to study the process of employment of persons with disabilities in terms of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Research by Mota et al (2020) confirmed that people with disabilities become self-employed entrepreneurs to avoid unemployment. For effective employment of disabled people there should be a comprehensive approach that includes a mechanism for interaction between different actors: employment services, educational institutions, public organizations, employers, medical and social expertise institutions (Arbuz, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
“…Research by Mota et al (2020) confirmed that people with disabilities become self-employed entrepreneurs to avoid unemployment. For effective employment of disabled people there should be a comprehensive approach that includes a mechanism for interaction between different actors: employment services, educational institutions, public organizations, employers, medical and social expertise institutions (Arbuz, 2018).…”
Section: Problem Statementmentioning
confidence: 99%